Particle size distributions determined by optical scanning and by sieving in the assessment of masticatory performance of complete denture wearers - Eberhard, Lydia; Schneider, Sophie; Eiffler, Constantin; Kappel, Stefanie; Giannakopoulos, Nikolaos Nikitas (Clinical oral investigations, 2015)
Objectives: Standard procedure for the measurement of masticatory performance is the fractionated sieving of fragmented test food, which is substantially time consuming. The aim of this study was to introduce a less laborious, comparable, and valid technique based on scanning. Methods: Fifty-six Optocal chewing samples were minced by wearers of complete dentures with 15 and 40 chewing strokes and analyzed by both a sieving and a scanning method. The sieving procedure was carried out using ten sieves (5.6, 4.0, 2.8, 2.0, 1.4, 1.0, 0.71, 0.5, 0.355, and 0.25 mm) and measuring the weight of the specific fractions. Scanning was performed with a flatbed scanner (Epson Expression1600Pro, Seiko Epson Corporation, Japan, 1,200 dpi). Scanned images underwent image analysis (ImageJ 1.42q, NIH, USA), which yielded descriptive parameters for each particle. Out of the 2D image, a volume was estimated for each particle. In order to receive a discrete particle size distribution, area–volume-conversion factors were determined. The cumulated weights yielded by either method were curve fitted with the Rosin–Rammler distribution (MATLAB, The MathWorks, Inc., Natick, USA) to determine the median particle size X 50. Results: The Rosin–Rammler distributions for sieving and scanning resembled each other and showed an excellent correlation in 15/40 chewing strokes (r = 0.995/r = 0.971, P < 0.01, Pearson’s correlation coefficient). The median particle sizes varied between 4.77/3.04 and 5.36/5.28 mm (mean 5.07/4.67) for scanning and 4.69/2.39 and 5.23/5.43 mm (mean 5.03/4.57) for sieving. On average, scanning overestimated the X 50 values by 1/2.4 %. The scanning method took 10 min per sample in contrast to 50 min for sieving. Conclusion: Optical scanning is a valid method comparable to sieving.